Etude théorique des composée ternaires CuInSe2 et CuInTe2 à l’aide decode Wien2K : Application photovoltaïque - الصادق, سليماني (University of El-Oued, 2021)
"In this work, we present the results of the structural, electronic, optical properties of CuInSe 2 and CuInTe2 ternary semiconductors using the FP-LAPW method, based on density functional theory (DFT), in the framework of the GGA approximation. The equilibrium lattice constants and the compressibility modulus for ternary compounds were calculated. The optimized structural equilibrium parameters (a, c) are in good agreement with the available results. Calculations of electronic properties show that ternary compounds are direct bandgap semiconductors. The dielectric function, the refractive index, the absorption coefficient and the reflectivity of the ternary compounds CuInSe2 and CuInTe2 as a function of the energy E in summer perform. the results obtained are in good agreement with other theoretical and experimental work available in the literature." "Dans ce travail, nous présentons les résultats des propriétés structurales, électroniques, optiques des semi-conducteurs ternaires CuInSe2 et CuInTe2 en utilisant la méthode FP-LAPW, basée sur la théorie de la fonctionnelle de la densité (DFT), dans le cadre de l'approximation GGA. Les constantes du réseau à l'équilibre et le module de compressibilité pour les composés ternaires ont été calculés. Les paramètres structuraux d'équilibre optimisés (a, c) sont en bon accord avec les résultats disponibles. Les calculs des propriétés électroniques montrent que les composés ternaires sont des semi-conducteurs à bande interdite directe. La fonction diélectrique, l'indice de réfraction, le coefficient d'absorption et la réflectivité des composées ternaires CuInSe2 et CuInTe2 en fonction de l’ énergie E en été effectuer . les résultats obtenue sont bon accord avec d’autre travaux théorique et expérimentale disponible dans les littératures."
Energies renouvelables en mecanique مذكرة ماستر تخصص
Keywords: FP-LAPW, DFT, WC-GGA, mBJ, photovoltaic, semicondictors.; FP-LAPW, DFT, WC-GGA ,mBJ, photovoltaïque et semi-conducteurs.